Quantification of changes in graft dimension after corrective osteotomy of the distal end of the radius - Bilić, R; Kovjanić, J; Kolundzić, R (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2005)
PURPOSE OF THE STUDY: This is a cross section retrospective study which shows undertaken in order to determine the frequency and degree of postoperative alterations in size of cortico-cancellous autografts used in corrective osteotomies of the distal radius. PATIENTS AND METHOD: In the period from 1987 to 2002, 50 patients (21 females and 29 males, mean age 38 years, range 18-64, were treated with corrective osteotomy, bone grafting and internal fixation after mal-united Colles' fracture. The patients were followed up from 6 months to 5 years (average 15 months). Heights of volar, ulnar, dorsal and radial sides of the graft were determined from radiographs (preoperative, immediately after the surgery and at the late follow-up examination) according to the BIZCAD method and put into the computer program, which compared them in three dimensions. RESULTS: In sixteen patients (32 %) one or more sides of the graft decreased in height during the postoperative period by more than three millimeters. In five cases there was a complete resorption of the implanted graft. In the other thirty-four cases, an average decrease in all sides of graft was statistically significant. Unequal decrease led to an increase of volar inclination angle of the distal articular surface of the radius, averaging 3 degrees. Influence of age on the diminution of the graft size was found. More distally placed grafts had less incidence of significant resorption. A correlation between initial height of the side of the graft and its alterations was also found (r=0.49, p<0.001). CONCLUSION: Postoperative changes in the size of graft are frequent and represent a serious obstacle to the success of corrective osteotomies. We recommend that: 1. the use of a the higher bone graft for elongating of the radius, however with a greater chance of resorption; the alternative method of ulna shortening should be considered; 2. the osteotomy line and the grafts should be placed more distally to decrease the risk of resorption; 3. if osteotomy can't be performed distally enough, postoperative immobilization for about three weeks should be considered.
Keywords: transplantace kostí; mladiství; Bone Transplantation; špatně zhojené fraktury; Radius; osteotomie; Middle Aged; fraktury vřetenní kosti; mužské pohlaví; Radius Fractures; radius; Adult; ženské pohlaví; Humans; lidé středního věku; Osteotomy; dospělí; Female; Adolescent; Fractures, Malunited; lidé; Male